2015
DOI: 10.14348/molcells.2015.2291
|View full text |Cite
|
Sign up to set email alerts
|

Setdb1 Is Required for Myogenic Differentiation of C2C12 Myoblast Cells via Maintenance of MyoD Expression

Abstract: Setdb1, an H3-K9 specific histone methyltransferase, is associated with transcriptional silencing of euchromatic genes through chromatin modification. Functions of Setdb1 during development have been extensively studied in embryonic and mesenchymal stem cells as well as neurogenic progenitor cells. But the role of Sedtdb1 in myogenic differentiation remains unknown. In this study, we report that Setdb1 is required for myogenic potential of C2C12 myoblast cells through maintaining the expressions of MyoD and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…While revising our manuscript, a recent paper by Song et al [ 66 ] claimed that Setdb1 knockdown in C2C12 proliferating myoblasts delayed terminal differentiation, whereas ectopic Setdb1 expression had only little effect. Thus, in order to study the role of Setdb1 in differentiation entry, we performed Setdb1 knockdown (KD) in confluent myoblasts in differentiation conditions.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…While revising our manuscript, a recent paper by Song et al [ 66 ] claimed that Setdb1 knockdown in C2C12 proliferating myoblasts delayed terminal differentiation, whereas ectopic Setdb1 expression had only little effect. Thus, in order to study the role of Setdb1 in differentiation entry, we performed Setdb1 knockdown (KD) in confluent myoblasts in differentiation conditions.…”
Section: Discussionmentioning
confidence: 86%
“…It is thus possible that Setdb1 could be part of the same complexes and undergo comparable regulation. However, Singh et al detected Trim28 but not Setdb1 in the MyoD complex and Song et al [ 66 ] failed to detect any interaction between Setdb1 and MyoD in co-immunoprecipitation assays. In addition, only 30/150 genes upregulated upon Trim28 knockdown where also upregulated (>2000 genes) upon Setdb1 KD (not shown).…”
Section: Discussionmentioning
confidence: 99%
“…HMT family members, which were first defined in 2002, allow euchromatic genes to mutate by mediating histone modification and complexing with proteins, such as SETDB1, CAP-1, HP1, DNMT3A/B, MBD1, and HDAC1/2 (Fritsch et al, 2010). SETDB1 proteins are associated with many biological processes, such as Barr bodies and embryogenesis, as well as gene silence Minkovsky et al, 2014;Song et al, 2015). Recent reports have revealed the SETDB1 protein's functional role in human carcinogenesis (Sun et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, surprisingly, overexpression of SETDB1 does not promote differentiation. 64 Another study indicated that SETDB1 promotes the expansion of muscle progenitor cells isolated from muscle fibers and its overexpression inhibits myogenic differentiation. Consistently, similar to G9a, knockdown of SETDB1 at the onset of differentiation led to enhanced differentiation.…”
Section: Function In Cellular Differentiation and Senescencementioning
confidence: 99%
“…Knockdown of SETDB1 reduces S phase cells and results in slower growth. 64 Genome wide analysis revealed SETDB1 occupancy correlated with H3K9me3 on target genes. Interestingly, SETDB1 occupancy was also apparent on promoters with active H3K9ac marks that did not correlate with H3K9me3.…”
mentioning
confidence: 99%